A Model for Spatially Varying Crime Rates in English Districts: The Effects of Social Capital, Fragmentation, Deprivation and Urbanicity - Congdon, Peter Douglas (International Journal of Criminology and Sociology, 2013)
Geographic variations in crime are often linked to aspects of urban social structure that are latent constructs, not directly observed but instead proxied by a range of observed indicators. Examples are area deprivation and urbanicity, both established risk factors for crime. Little UK based evidence exists for impacts on crime of other potentially relevant influences such as social capital and social fragmentation, which are also latent constructs. Other cited influences on area crime differences include income inequality, but there may be further unobserved factors, which tend to be spatially correlated. The present paper seeks to establish, using appropriate multivariate and spatial regression techniques, the relative importance of social capital, fragmentation, deprivation, urbanicity and income inequality in an analysis of recent crime variations between 324 English Local Authority Districts. Variations in total, violent and property crime are considered.